Assertive speech acts of persuasion in English presidential election speeches - Nguyen, Thanh Thanh (Technium Social Sciences Journal, 2022)
Politics is a process of making decisions by the distribution of power and resources in order to put certain political, economic and social ideas into practice. For political messages to be delivered to the target community through political discourse, many strategies have been employed to fulfill the purpose of persuading to the audience. The study investigates the assertive speech acts of persuasion utilized in Hillary Clinton and Donald Trump’s 2016 presidential election speeches. Adopting the speech act theory by Searle (1980), the study aims to uncover the features of assertive speech acts used by the two politicians for persuasion. The data was analyzed using descriptive qualitative method basing on quantitative information. The findings showed that the process of manipulation of the two politicians was fostered by assertive speech acts highlighting the illocutionary forces of asserting, affirming, avowing, denying, asserting not, and propounding. Through the illocutionary forces, both Trump and Clinton would like to communicate their different political stands and ideologies to persuade the audience to advocate them. Donald Trump spread his persuasion with more dominating frequencies of assertive speech acts than Hillary Clinton. Besides, they also demonstrated distinctively different illocutionary acts addressing different issues to serve their political purposes.